Relative cost-effectiveness of using an extensively hydrolyzed casein formula containing the probiotic Lactobacillus rhamnosus GG in managing infants with cow’s milk allergy in Spain - Guest JF; Weidlich D; Mascuñán Díaz JI; Díaz JJ; Ojeda PM; Ferrer-González JP; Gil D; Onrubia I; Rincón Víctor P (Dove Medical Press, 2015)
Julian F Guest,1,2 Diana Weidlich,1 J Ignacio Mascuñan Díaz,3 Juan J Díaz,4 Pedro Manuel Ojeda,5 J Pablo Ferrer-González,6 David Gil,7 Isabel Onrubia Vaquero,8 Pedro Rincón Victor9 1Catalyst Health Economics Consultants, Northwood, Middlesex, 2Faculty of Life Sciences and Medicine, King’s College, London, UK; 3Centro de Salud de Paterna, Valencia, Spain; 4Hospital Universitario Central de Asturias, Oviedo, 5Clínica de Asma y Alergia Doctores Ojeda, 6Hospital General de Requena, Valencia, 7Hospital Universitario Virgen de la Arrixaca, Murcia, 8Centro de Salud Valle de la Oliva, Majadahonda, 9Centro de Salud la Chopera, Alcobendas, Spain Objective: To estimate the cost-effectiveness of using an extensively hydrolyzed casein formula containing the probiotic Lactobacillus rhamnosus GG (eHCF + LGG; Nutramigen LGG) as a first-line management for cow’s milk allergy compared with eHCF alone, and amino acid formulae in Spain, from the perspective of the Spanish National Health Service (SNS).Methods: Decision modeling was used to estimate the probability of immunoglobulin E (IgE)-mediated and non–IgE-mediated allergic infants developing tolerance to cow’s milk by 18 months. The models also estimated the SNS cost (at 2012/2013 prices) of managing infants over 18 months after starting a formula as well as the relative cost-effectiveness of each of the formulae.Results: The probability of developing tolerance to cow’s milk by 18 months was higher among infants with either IgE-mediated or non–IgE-mediated allergy who were fed eHCF + LGG compared with those fed one of the other formulae. The total health care cost of initially feeding infants with eHCF + LGG was less than that of feeding infants with one of the other formulae. Hence, eHCF + LGG affords the greatest value for money to the SNS for managing both IgE-mediated and non–IgE-mediated cow’s milk allergy.Conclusion: Using eHCF + LGG instead of eHCF alone or amino acid formulae for first-line management of newly-diagnosed infants with cow’s milk allergy affords a cost-effective use of publicly funded resources because it improves outcome for less cost. A randomized controlled study showing faster tolerance development in children receiving a probiotic-containing formula is required before this conclusion can be confirmed.Keywords: amino acid formula, cost-effectiveness, cow’s milk allergy, extensively hydrolyzed formula, Spain, Lactobacillus rhamnosus GG